Pengaruh Cara Booster terhadap Efikasi Vaksinasi Oral dengan Debris Sel Aeromonas hydrophila pada Lele Dumbo (Clarias sp.) - Dini Siswani Mulia; Rachmansyah Rachmansyah; Triyanto Triyanto (Universitas Gadjah Mada, 2006)
The aims of this research were to evaluate the effect of booster on the efficacy of vaccination with cell debris of Aeromonas hydrophila. Catfish (Clarias sp.) (10-13 cm of total length) were used for experiment with 4 treatments, i.e. (1) OS: oral vaccination and injection booster; (2) OO: oral vaccination and oral booster; (3) OR: oral vaccination and immersion booster; (4) without vaccination and booster (control). Booster was conducted one week after vaccination. The challenge test was conducted two weeks after booster. The results showed that the survival rate, Relative Percent Survival (RPS), Mean Time to Death (MTD), and antibody titer of OS treatment was significantly different (P<0.05) with OO, OR, and control. The survival rate and RPS of fish vaccinated by OS treatment reached 100%. The highest antibody titer was 2048 for OS treatment. The result sugested that oral vaccination followed by booster injection was the most effective method of vaccination.